2017
DOI: 10.1016/j.jhep.2017.06.026
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic factors and predictors of sorafenib benefit in patients with hepatocellular carcinoma: Analysis of two phase III studies

Abstract: This exploratory pooled analysis showed that treatment with sorafenib provides a survival benefit in all subgroups of patients with HCC; however, the magnitude of benefit is greater in patients with disease confined to the liver (without extrahepatic spread), or in those with hepatitis C virus, or a lower neutrophil-to-lymphocyte ratio, an indicator of inflammation status. These results help inform the prognosis of patients receiving sorafenib therapy and provide further refinements for the design of trials te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

44
380
5
15

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(459 citation statements)
references
References 45 publications
44
380
5
15
Order By: Relevance
“…Notably, this clinical course is in line with data from the CheckMate 040 trial [9], where responses occurred early in treatment and were long-lasting (median duration of response 17 months). Only recently, different groups identified the presence of HCV as a positive predictor for sorafenib efficacy in patients with HCC [12]. In line with this, we initiated a first-line therapy with sorafenib in our patient suffering from HCV-related liver cirrhosis.…”
Section: Discussion/conclusionmentioning
confidence: 72%
“…Notably, this clinical course is in line with data from the CheckMate 040 trial [9], where responses occurred early in treatment and were long-lasting (median duration of response 17 months). Only recently, different groups identified the presence of HCV as a positive predictor for sorafenib efficacy in patients with HCC [12]. In line with this, we initiated a first-line therapy with sorafenib in our patient suffering from HCV-related liver cirrhosis.…”
Section: Discussion/conclusionmentioning
confidence: 72%
“…Finally, as sorafenib treatment is expensive, its associated cost represents a limitation [5]. Although several studies have investigated predictive biomarkers of sorafenib efficacy, there have been no established predictive biomarkers [6-9]. Therefore, a simple biomarker for the prediction of sorafenib efficacy would be clinically advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that the impact of sorafenib is largely confined to the patients who are HCV positive [25,26]. The present NMA cannot account for this specific aspect to be ascertained, and the investigation of this issue would require subgroup efficacy and safety data segregated for HCV positive and negative patients.…”
Section: Discussionmentioning
confidence: 95%